2019
DOI: 10.1017/s002185961900073x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and crop rotations enhance populations of earthworms, termites, dung beetles and centipedes: evidence from a long-term trial in Zambia

Abstract: Macro-organisms contribute significantly to soil fertility improvement. The influence of conservation agriculture (CA) in southern Africa on their populations has not yet been fully understood. Thus, the objective of the current study was to evaluate the effects of CA and conventional tillage on below ground biological activity in a CA long-term trial in Monze, Zambia from 2011 to 2013. The study had ten treatments which differed by tillage systems (conventional ploughing, planting basins and direct seeding) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…pared to the TA practices due to the absence of physical damage caused by soil tillage, which was congruent with different studies [22,51,52]. It was probably due to the higher CA soil moisture [19,53,54] than in the TA, 10.89 ± 0.72 and 9.93 ± 0.51%, respectively (Figure 4), and cover crop in the CA presented 0.24 ± 0.06 kg m −2 of Desmodium sp., which served as a food source for earthworms [19]. Analogously, the number of earthworms m −2 reported by McInga et al, Nurul Aini et al, and Birkás et al [18,53,55] in the CA soils was higher by 24, 17, and 52 earthworms m −2 , respectively, than in the TA soils, probably due to the elimination of tillage and the presence of crop stubble on the soil, conditions that provided a suitable abiotic environment for the development of earthworms [54].…”
Section: Earthworm Populationsupporting
confidence: 87%
See 1 more Smart Citation
“…pared to the TA practices due to the absence of physical damage caused by soil tillage, which was congruent with different studies [22,51,52]. It was probably due to the higher CA soil moisture [19,53,54] than in the TA, 10.89 ± 0.72 and 9.93 ± 0.51%, respectively (Figure 4), and cover crop in the CA presented 0.24 ± 0.06 kg m −2 of Desmodium sp., which served as a food source for earthworms [19]. Analogously, the number of earthworms m −2 reported by McInga et al, Nurul Aini et al, and Birkás et al [18,53,55] in the CA soils was higher by 24, 17, and 52 earthworms m −2 , respectively, than in the TA soils, probably due to the elimination of tillage and the presence of crop stubble on the soil, conditions that provided a suitable abiotic environment for the development of earthworms [54].…”
Section: Earthworm Populationsupporting
confidence: 87%
“…When tillage begins, soil experiences fractures that break its structure; organic matter oxidation, runoff [14], and bulk density [15] increase; and hydraulic conductivity and water content decrease, leading to soil erosion [16,17]. Furthermore, tillage creates an adverse environment for soil macrofauna due to inadequate temperature, soil humidity, and lower carbon availability, which decreases the earthworm population [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in central Mexico, Castellanos-Navarrete et al [84] showed that CA produced an evident increase in the abundance and biomass of earthworms compared to CT. Sharma and Dhaliwal [309], in a study of rice-wheat cropping systems in South Asia, concluded that a zero-tillage system with crop residue retention improved micronutrient contents and provided feeding for soil macrofauna, especially earthworms, as compared to conventional tillage without residue. In a long-term trial in Zambia, Muoni et al [310] concluded that reduced tillage systems and crop rotations increase biological activity, with the density of termites and earthworms being higher in CA systems than in CT systems. Henneron et al [282] reported an increase in anecic earthworms in the long term in CA systems.…”
Section: Earthwormsmentioning
confidence: 99%
“…No-tillage and crop residue retention encourage soil life and microbial activity benefiting both above and below ground biodiversity (Mashavakure et al, 2019; Mhlanga et al, 2020; Muoni et al, 2019). Research by Muoni et al (2019) and Thierfelder and Wall (2010) confirmed that no-tillage with residue cover significantly increases the abundance of earthworms which are most important to develop a conducive soil pore structure (Kladviko, Griffith and Mannering, 1986a; Kladviko, Mackay and Bradford, 1986b). A positive outcome of ground burrowing macro-fauna is improved infiltration into deeper layers and an increase in available soil moisture for plant growth in times of in-season dry spells or droughts (Mhlanga and Thierfelder, 2021).…”
Section: The Issue Of Residue Retention In Mixed Crop/livestock Systemsmentioning
confidence: 99%